Pengaruh Lingkungan Kerja Dan Kemampuan Penguasaanteknologi Terhadap Kinerja Karyawan Pada Perusahaan PT. Semen Tonasa Kabupaten Pangkep - Risdayanti Risdayanti; Nurdin Latif; Baharuddin Baharuddin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to determine the influence of the work environment and technological ability on employee performance at PT. Semen Tonasa Pangkep Regency. The method used in this research is a quantitative method with the number of respondents being 75 employees who were used as samples using a sampling technique, namely a saturated sample, where the data collection technique used a questionnaire. The analysis used in this research is a multiple linear regression test. Simultaneous test results of work environment variables and ability to master technology have a positive and significant effect on employee performance variables as proven based on simultaneous test results with a significance value of f<α (0.000<0.05). Partial test results for work environment variables have a positive and significant influence on employee performance variables with a significance value of f<α (0.000<0.05). Partial test results for technology mastery ability variables have a positive and significant influence on employee performance with a significance value of f<α ( 0.001<0.05)